Fracture strength of bovine incisors after intra-radicular treatment with MTA in an experimental immature tooth model - Bortoluzzi, E. A.; Souza, E. M.; Reis, José Mauricio dos Santos Nunes [UNESP]; Esberard, R. M.; Tanomaru-Filho, M. (Blackwell Publishing, 2007)
Aim To evaluate, using an experimental immature tooth model, the fracture resistance of bovine incisors submitted to different reinforcement treatments with mineral trioxide aggregate (MTA).Methodology An immature tooth model was created by sectioning the coronal and apical portions of 40 bovine incisors 8 mm above and 12 mm below the cementoenamel junction. The root canals were irrigated with 1.0% sodium hypochlorite. They were enlarged both coronally and apically using number 703 carbide burs (ISO: 500-104-168-007-021) and their internal diameter was standardized to 2.1 mm. The specimens were assigned to four groups (n = 10): GI-control (without filling); GII-apical MTA plug + filling with gutta-percha and endodontic sealer; GIII-filling with MTA; GIV-apical MTA plug + filling with MTA + metallic post (Reforpost I). A polyether impression material was used to simulate the periodontal ligament. The specimens were submitted to a compressive load at a crosshead speed of 0.5 mm min(-1) in a servo-hydraulic universal testing machine (MTS 810) applied at 45 degrees to the long axis of the tooth until failure. Data were submitted to statistical analysis by the Kruskal-Wallis test at 5% significance level.Results GIV presented the highest fracture resistance (32.7N) and differed significantly from the other groups (P < 0.05). No statistically difference was found between GII (16.6N) and GIII (23.4N) (P > 0.05). GIII had a significantly higher fracture resistance than GI (P < 0.05).Conclusions the use of MTA + metallic post as an intra-radicular reinforcement treatment increased the resistance to fracture of weakened bovine teeth in an experimental immature tooth model.
Keywords: apexification; bovine teeth; fracture resistance; metallic post; mineral trioxide aggregate